ENVIRONMENTAL AND SUSTAINABILITY ISSUES IN THE PALM OIL SECTOR: ANALYSIS OF THE IMPACT OF LOCAL REGULATIONS AND GOVERNMENT POLICIES ON ENVIRONMENTAL MANAGEMENT, NATURAL RESOURCE CONSERVATION, AND THE SOCIO-ECOLOGICAL SUSTAINABILITY OF LOCAL COMMUNITIES - Loso Judijanto (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2026)
This study analyses the impact of local regulations and government policies on environmental management, natural resource conservation, and the socio-ecological sustainability of local communities in Indonesia's palm oil sector. Through a review of existing literature, this study reveals that regulatory instruments have great potential to control deforestation, reduce pollution, and protect sensitive ecosystems. However, their implementation is often hampered by overlapping authorities, weak supervision, and a lack of alignment between economic and environmental policies, meaning that environmental management and natural resource conservation are not always achieved optimally. The impact of regulations on the socio-ecological sustainability of local communities is also ambivalent. On the one hand, plasma schemes, CSR, and community dialogue obligations through ISPO can increase income, access to infrastructure, and community participation in resource management. On the other hand, in many areas, regulations actually reinforce inequality, ignore customary rights, and trigger agrarian conflicts, especially in areas that still depend on subsistence and forest ecosystems. The results of the study show that the same regulations can produce very different results depending on the socio-ecological context and the quality of implementation at the local level. Overall, this study concludes that regulations in the palm oil sector have significant potential to promote better environmental management, natural resource conservation, and the socio-ecological sustainability of local communities, but only if they are implemented consistently, inclusively, and based on evidence. Strengthening coordination between levels of government, strengthening the capacity of supervisors, recognising customary rights, and integrating local knowledge are important prerequisites for regulations to not only become a formal instrument, but to truly be able to create a balance between economic growth, environmental protection, and social justice for local communities.